Vídeo-artroscopia da articulação fêmorotibiopatelar de cães antes e 21 dias após secção do ligamento cruzado cranial (estudo experimental). - Natalie Ferreira Borges (2006)
The Cranial cruciate ligament rupture is a common and significant lesion in dogs, and its instability can lead to the development of degenerative changes. The objective of this study was to evaluate, through video-arthroscopy, the changes of the stifle joint 21 days after the experimental rupture of the CCL, using as a reference the parametersfound immediately in the arthoscopic examination right before the rupture. 18 dogs were used, all of them mongrel dogs, of both genres, with weight between 18 and 25 kg, they were submitted to an arthroscopic evaluation and subsequent experimental rupture of the CCL, and guided by arthroscopy. The stifles structures were inspected from the lateral joint pouch, the lateral condyle, the origin tendol of the long digital extensor muscle, the intercondylar region, the tibial plateau, the menisci and ligaments, the medial joint pouch, the medial condyle, the femoropatellar joint and the suprapatellar joint pouch. The animals were maintained at individual kennels for 21 days and submitted to a new arthroscopic evaluation in which the joint structures were inspected as previously described. The arthroscopic examination at the 21st day , made possible to visualize and to document the remaining of CCL and joint changes such: increase of the hyperemia and synovial proliferation increase in the synovial membranes, as well as fibrillation and irregularities in the joint surfaces and osteophyte formation, mainly of the femoral condyles, trochlear ridges and the intercondylar region respectively. These results suggest that arthroscopy is a necessary method for macroscopic evaluation of the smooth and bone joint tissues, revealing itself as a safe method to diagnose and to follow the joint changes.